Analysis of steam generator tube rupture accident for Korean reactor APR1400 - Le , Dai Dien; Le , Tri Dan (Nuclear Science and Technology, 2013)
The APR1400 is an advanced light water reactor designed by KEPCO, Korea. Steam generator tube rupture (SGTR) is one of the design basic accidents (DBA) which needs to be analyzed in safety analysis report. In this paper, a steam generator tube rupture event was simulated by using RELAP/SCDASIM system code and some results are compared with MARS code with modeled MULTID components of the reactor vessel and two steam generators. Further simulations for tube rupture depend on the broken positions and number of ruptured tubes is also estimated. The results are in fairly good agreement with one simulated by MARS code.